Digital Literacy of Senior High School Science Students: A Case Study of Technology Use in Daily Academic Life - Nurdiyanti, Nurdiyanti; Anisa, Anisa; Ananthakkarasu, Virginie (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Fundamental Finding: High school students spend over six hours daily on digital devices, primarily for entertainment and learning purposes. While educational use is significant, entertainment remains the dominant activity. Students prefer easily accessible information but often lack strong habits for verifying content credibility. Online platforms such as Google Classroom and Moodle are seen as helpful, despite occasional technical and connectivity issues. Students demonstrate awareness of personal data protection and use apps like CapCut to create learning content. Although students view online collaboration positively, they still face certain challenges in its implementation. Implication: Digital technology plays a crucial role in supporting student learning, but there is a need to improve digital literacy and address technology dependence and connectivity problems to optimize its benefits. Limitation: This study focuses on students’ usage patterns without exploring psychological or socio-economic factors influencing technology use. Future Research: Future studies should investigate the effects of technology dependence on student well-being and develop more effective digital literacy programs, including comparative analyses across different regions.